Factors Related to Small Scale Beef Fattening Programs in Dinajpur District of Bangladesh (Progressive Agriculture, 2013)
The experiment was conducted to investigate the factors related to small scale beef fattening programs in three upazilas (Birganj, Kaharul, and Khansama) under Dinajpur district of Bangladesh. Data were collected using an interview schedule from randomly selected 75 farmers who were involved in small scale beef fattening programs. In this study out of the 75 farmers 54.7% are involved in agriculture, 26.7% in business, 13.3% in service and 5.3% in beef fattening. About 44.7% farmers fattened beef for 3 months. Fifty six percent farmers used own capital for beef fattening, 24% took bank loan and remaining farmers lending from others sources. About 57.3% farmers had taken short training on beef fattening whereas about 42.7% did not take any training on beef fattening. More than 34.7% farmers used beef fattening tablets, 28.0% Urea Molasses Straw (UMS), 26.7% used Urea Molasses Block (UMB) in beef fattening. Sixty six percent farmers reported shortages of animal feed, 50% reported lack of credit and 93.3% reported high cost of feed as the major problems of small scale beef fattening. In conclusion, the result of present study would be useful information to farmers and researchers to identify the management of small scale beef fattening practices in Bangladesh.DOI: http://dx.doi.org/10.3329/pa.v23i1-2.16563Progress. Agric. 23(1 & 2): 33 38, 2012